Penerapan Media Loose Part dalam Pembelajaran Keaksaraan Awal pada Masa Pandemi Covid-19 - Sunarti Sunarti; Mukti Widayati; Nurnaningsih Nurnaningsih (Departement of Mathematics Education, 2023)
The purpose of this research is to: 1) describe the lesson plan. 2) describe the implementation of learning. 3) describe learning barriers. 4) describe early literacy learning solutions using Loose part media during the pandemic at Mojoreno Kindergarten, Sidoharjo District, Wonogiri Regency. This type of research is a type of descriptive qualitative research. The research approach is a fixed case study type. The location of the research was carried out at Mojoreno Kindergarten, Sidoharjo District, Wonogiri Regency. The time of research was in semester II of the 2021/2022 school year, with the object of research being group B students at Mojoreno Kindergarten, a total of 15 children. Sources of data in this study come from documents, events and activities as well as places and locations of research. Data collection techniques in the form of in-depth interviews, observation and document analysis. The data validation technique in this study was triangulation, namely source triangulation and method triangulation. Data analysis was performed using an interactive model. The research carried out shows that: 1) learning plans that contain learning steps, 2) implementation of learning that is in accordance with the prepared lesson plans, 3) the emergence of obstacles in learning that Loose part media 4) solutions to overcome obstacles encountered, namely working with parents of students in preparing media and documenting learning outcomes or by using small notes to record children's progress.